Molecular Transport within Polymer Brushes: A FRET View at Aqueous Interfaces - Besford, Quinn A.; Schubotz, Simon; Chae, Soosang; Özdabak Sert, Ayşe B.; Weiss, Alessia C. G.; Auernhammer, Günter K.; Uhlmann, Petra; Farinha, José Paulo S.; Fery, Andreas (MDPI AG, 2022)
Molecular permeability through polymer brush chains is implicated in surface lubrication, wettability, and solute capture and release. Probing molecular transport through polymer brushes can reveal information on the polymer nanostructure, with a permeability that is dependent on chain conformation and grafting density. Herein, we introduce a brush system to study the molecular transport of fluorophores from an aqueous droplet into the external “dry” polymer brush with the vapour phase above. The brushes consist of a random copolymer of N-isopropylacrylamide and a Förster resonance energy transfer (FRET) donor-labelled monomer, forming ultrathin brush architectures of about 35 nm in solvated height. Aqueous droplets containing a separate FRET acceptor are placed onto the surfaces, with FRET monitored spatially around the 3-phase contact line. FRET is used to monitor the transport from the droplet to the outside brush, and the changing internal distributions with time as the droplets prepare to recede. This reveals information on the dynamics and distances involved in the molecular transport of the FRET acceptor towards and away from the droplet contact line, which are strongly dependent on the relative humidity of the system. We anticipate our system to be extremely useful for studying lubrication dynamics and surface droplet wettability processes.
Keywords: polymer brushes; FRET; molecular transport; spatially-resolved; wettability; Polymers; spatially-resolved; wettability; Organic chemistry; Water; molecular transport; polymer brushes; Article; Solutions; QD241-441; FRET; Fluorescence Resonance Energy Transfer; Wettability